1962
DOI: 10.1071/ar9620443
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of parasites of oriental fruit fly (Dacus dorsalis) against Queensland fruit fly (Strumeta tryoni)

Abstract: In 1950, a programme was initiated to utilize against the Queensland fruit fly (Strumeta tryoni) parasites which were introduced during 1948–1950 into Hawaii, where they produced a considerable reduction in the incidence of oriental fruit fly (Dacus dorsalis). The present paper describes the work carried out under this programme up to October 1959. During 1951–1957 the emphasis was on rearing, at Sydney, on Queensland fruit fly, stocks of Opius longicaudatus and O. oophilus from small stocks imported from Hawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The trees were 3–4 m tall and the orchard was insecticide free. Nectarine is one of the most preferred hosts of B. tryoni (Fitt 1986), which in turn is one of the most common hosts of D. kraussii (Snowball et al . 1962).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trees were 3–4 m tall and the orchard was insecticide free. Nectarine is one of the most preferred hosts of B. tryoni (Fitt 1986), which in turn is one of the most common hosts of D. kraussii (Snowball et al . 1962).…”
Section: Methodsmentioning
confidence: 99%
“…2010). In Australia there are field and laboratory records of D. kraussii attacking the economic fruit flies Bactrocera tryoni (Froggatt), B. neohumeralis (Hardy) and B. jarvisi (Tryon) (Snowball et al . 1962; Ero et al .…”
Section: Introductionmentioning
confidence: 99%
“…through parasitism by an infected wasp (although wasp DNA was not detected in the larva). Fopius arisanus is native to the Asia-Pacific, introduced to Australia in 1956 (Snowball et al, 1962), and is not a demonstrated parasitoid of B. frauenfeldi. However, it is a known parasitoid of 17 species of Bactrocera, including B. cacuminata, and other Fopius species are known to parasitize B. frauenfeldi (Carmichael et al, 2005).…”
Section: Horizontal Transmission Of Wolbachia Between Australian Tephmentioning
confidence: 99%
“…The failure of D. kraussii to successfully develop from B. cacuminata casts doubt on previous records that the fly is a host for this wasp (Snowball et al. 1962; Snowball & Lukins 1964; Snowball 1966; Wharton & Gilstrap 1983; Waterhouse 1993; Carmichael et al.…”
Section: Discussionmentioning
confidence: 86%